Optical coherence tomography: a reliable alternative to invasive histological assessment of acute wound healing in human skin?3. (April 2014) - Greaves, N.S.; Benatar, B.; Whiteside, S.; Alonso‐Rasgado, T.; Baguneid, M.; Bayat, A.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Optical coherence tomography is an emerging imaging technology that has proved useful in diagnosis and monitoring of inflammatory dermatological conditions. What does this study add? Characteristic architectural changes that correlate with histological phases of cutaneous wound healing can be identified with OCT. OCT‐derived mean greyscale values may represent a novel measure of wound fibrosis. Noninvasive OCT could be used as an alternative to histology in wound assessment, thereby reducing the need for tissue biopsies.